(untitled) (Communications in Inorganic Synthesis, 2014)
Five water soluble silver(I)Â complex with Ibuprofen (AgIbu), Naproxen (AgNap),Â Mefenamic acid (AgMef), acetyl salicylic acid(AgAsp) and salicylic acid (AgSal) were synthesized and characterized by elemental analysis, FT-IR, 1H and 13C NMR. Data suggest coordination of the ligand to Ag(I) through the oxygen atom of the carboxylic group. AgAsp was obtained as a mixture of AgAsp and Ag(I)-2-hydroxybenzoate (AgSal) due to decomposition by thermal and hydrolysis of acetylsalicylic acid into salicylic acid. AgSal structure was confirmed by FT-IR, NMR and X-ray diffraction. Synthesized compounds were tested toward UV-radiation (258 nm, 30 W) and compared with AgCl in order to characterize their light sensibility.